Mass screening of COVID-19 cases by sputum testing: An Indian perspective - Sheikh Mohd Saleem (Wolters Kluwer Medknow Publications, 2021)
SARS CoV 2 virus is detected in the respiratory tract by using nasal/oropharyngeal and nasal mid-turbinate swabs, nasopharyngeal wash and aspirate, and an oral aspirate. The anterior nares are the most common place to collect samples due to its ease and little invasiveness. Sample collection requires experienced hands, and if the appropriate technique isn't followed, it might lead to false negative results and alter the final conclusion. Because of its size and robustness, India's healthcare system has over 700 districts each running National Tuberculosis Elimination Program (NTEP) and experts in India have proposed modifying the CBNAAT machines used in NTEP program for COVID 19 testing by utilizing a new cartridge. After a second wave of COVID-19 cases, the number of cases in India is on the rise again. When dealing with a highly contagious disease, healthcare professionals are constrained by a lack of personal protective equipment, logistics, and infrastructure. The nasopharyngeal specimen and the procedure involved, make it a more difficult and riskier affair for healthcare practitioners to perform. If COVID-19 is combated with the NTEP's current infrastructure, human resources, and logistics, we believe that early detection of cases and overall containment will be maximized. Sputum samples can be self-collected in small plastic containers and sent to the nearest tuberculosis unit for CBNAAT analysis instead of using the professional technique of collecting nasopharyngeal swabs in Viral Transport Media. Sputum sample collection is a simple operation. Be it in urban tertiary care facilities or a rural subcentre. To collect sputum, healthcare staff can simply assist. In the current phase of the pandemic in India, where the majority of COVID-19 infections are asymptomatic, mass screening at the community level using effective testing specimens and methodologies becomes critical and the only choice. It would make sense to collect COVID-19 samples at the community level based on the scientific evidence in such a scenario, especially for a country with a population of over 1.3 billion people.